On the application of multi-agent systems in buildings for improved building operations, performance and smart grid interaction – A survey. (October 2015) - Labeodan, Timilehin; Aduda, Kennedy; Boxem, Gert; Zeiler, Wim
Abstract: Toward efforts to improve sustainability of energy supply and to achieve worthwhile reduction in greenhouse gas emissions, in addition to the increased use of renewable energy sources in buildings, more emphasis is being placed on the need for improved control, management and coordination of building operations and its interaction with the smart-grid. Multi-agent system (MAS), due to its distributed and autonomous properties is considered a viable tool for improving the coordination and management of interactions between buildings and components of the smart-grid. This paper provides an overview of the application of multi-agent systems in building operations for coordination of various building processes and buildings interaction with the smart-grid. By first reviewing the notions of agents, its potentials and key attributes, the paper identifies key areas in building operation where its application provides improved performance. Furthermore, the paper provides a discussion on the knowledge gaps, challenges with its uptake in practical building application as well as opportunity for concentrated research.